Stabilization of a hypersonic boundary layer using a felt-metal porous coating. (25th March 2015) - Tritarelli, R. C.; Lele, S. K.; Fedorov, A.
Abstract : An error in the complex representation of the porous-coating model used in the study by Fedorov et al . ( J. Fluid Mech., vol. 479, 2003, pp. 99–124), investigating the stabilization effect of ultrasonically absorptive coatings on hypersonic boundary layers, is pointed out and corrected. This error has been acknowledged by Fedorov et al . ( J. Fluid Mech., vol. 769, 2015, pp. 725–728). The corrected version of the erroneous linear stability results of the original work is presented and previously made conclusions are reassessed. The novel numerical results indicate that second-mode instabilities are shifted to lower frequencies on felt-metal porous coatings, similar to the behaviour observed on porous coatings with regular microstructure.